General practitioners’ barriers to cross-sectoral collaboration on pregnant women with vulnerabilities: a cross-sectional survey in Danish general practice - Louise Brygger Venø; Line Bjørnskov Pedersen; Jens Søndergaard; Ruth Kirk Ertmann; Dorte Ejg Jarbøl (Scandinavian Journal of Primary Health Care)
Background Pregnancy vulnerability contributes to poor perinatal mental health. Proper cross-sectoral collaboration may mitigate perinatal mental health problems. General practitioners (GPs) often face barriers when assessing pregnancy vulnerability, but little is known about GPs’ perceived barriers to the cross-sectoral collaboration on vulnerable pregnant women.Objective To explore GPs’ barriers to cross-sectoral collaboration on pregnant women with vulnerabilities, and how barriers are associated with the organization of antenatal care (ANC) and general practice characteristics.Design, setting and subjects A cross-sectional questionnaire study among Danish GPs (n = 3465).Main outcome measures Descriptive statistics according to the Theoretical Domains Framework describes the barriers to collaboration. Analytical statistics with ordered logistic regression models demonstrate associations between selected barriers (the main outcome measures) and organization of ANC, GP and practice, characteristics.Results A total of 760 GPs (22%) participated. Perceived GP barriers to collaboration were lacking knowledge of ANC levels relevant to vulnerable pregnant women, insufficient information on vulnerability indicators from collaborating parties, heavy workload and insufficient remuneration for collaborative meetings. Being young were associated with insufficient GP knowledge of ANC levels. Old age was associated with less likelihood of experiencing heavy workload as a barrier.Conclusions Barriers to collaboration on vulnerable pregnant women were associated with some GP-organizational characteristics including low experience in collaborating with partners in ANC, and GP characteristics, such as age. Reducing general practice workload, e.g. by reorganizing priority areas, releasing more time to vulnerable patients, and improving cross-sectoral information sharing on vulnerability might improve collaboration on vulnerable pregnant women.